Factors Influencing Monkeypox Vaccination: A Cue to Policy Implementation - Priyobrat Rajkhowa; Viola Savy Dsouza; Rashmi Kharel; K. Cauvery; B. Rashmi Mallya; D. S. Raksha; V. Mrinalini; Preejana Sharma; Sanjay Pattanshetty; Prakash Narayanan; Chandrakant Lahariya; Helmut Brand (Springer, 2023)
Abstract Background Following the mpox 2022 outbreak, several high-income countries have developed plans with inclusion criteria for vaccination against the mpox disease. This study was carried out to map the factors influencing mpox vaccination uptake to help address the challenges and increase vaccination confidence. Methods This was a study based on Tweet analysis. The VADER, Text Blob, and Flair analyzers were adopted for sentiment analysis. The "Levesque conceptual framework for healthcare access" was adopted to evaluate the factors impacting access and the decision to get mpox vaccination. Consolidated Criteria for Reporting Qualitative Research (COREQ) criteria were adopted. Findings A total of 149,133 tweets were extracted between 01/05/2022 and 23/09/2022. Around 1% of the random tweets were used for qualitative analysis. Of the 149,113, tweets were classified as positive, negative and neutral, respectively, by (a) VADER: (55,040) 37.05%, (44,395) 29.89%, and (49,106) 33.06%, (b) TextBlob: (70,900) 47.73%, (22,729) 15.30%, and (54,921) 36.97%, and (c) Flair: (31,389) 21.13%, (117,152) 78.87%, and 0.00%. Sentiment trajectories revealed that communication, stigmatization, accessibility to and availability of vaccines, and concerns about vaccine safety as factors influencing decision-making in the content and flow of tweets. Interpretation Twitter is a key surveillance tool for understanding factors influencing decisions and access to mpox vaccination. To address vaccine mistrust and disinformation, a social media-based risk communication plan must be devised. Adopting measures to remove logistical vaccination hurdles is needed. Obtaining fact-based information from credible sources is key to improving public confidence.